The principled slope: religious freedom and the European Court of Human Rights. Issue 3 (2nd October 2017) - Adrian, Melanie
ABSTRACT: This contribution examines four cases, Dahlab v. Switzerland, Şahin v. Turkey, SAS v. France and Ebrahimian v. France, handed down by the European Court of Human Rights (ECtHR) between 2001 and 2015. The ECtHR has increasingly prohibited women from wearing the headscarf and face veil in public spaces. I argue that the rationale used to support these limitations has progressively moved away from an adjudication of harm and evaluation of the facts, to emphasising general principles and creating vague new legal concepts. This trend is problematic because appealing to general principles lessens the requirement of member states to present a fact-based case that carefully weighs trade-offs on key issues such as religious freedom vis-à-vis diversity and pluralism. This tendency also makes it easier for the Court to expand the already widening application of the margin of appreciation to states.